Peningkatan Kesadaran Orang Tua untuk Perencanaan Keuangan Pendidikan Anak di Kota Semarang - Amilahaq, Farikha; Hastuti, Erma Sri; Putri, Erlinda Ramadhani Permata; Astuti, Sintya Nur; Rizkiyani, Anisa (Penerbit Goodwood, 2025)
Purpose: The community service program aims to increase parents’ awareness, especially mothers, regarding the importance of planning children's education and finances. Methodology/approach: The program was implemented in the RT 02 RW 08 area of Pedurungan Lor Village, Semarang City. Specifically, the activity was presented by mothers who were members of the RT 02 RW 08 PKK Group. The method used was socialization about the challenges and benefits of children's education, followed by a survey of parental awareness regarding children's education and planning. Results/findings: The program was conducted with 21 participants, of which only 14 percent were college graduates, while 86 percent had lower education levels. The data show that the participants understand that education for children up to college is very important and needs to be pursued. The implementation of the activity also facilitated participants with smart wallets to help them manage their family finances. Conclusion: Parents believe in the importance of education for their children, but this is not followed by an affirmative action to increase children's awareness of the importance of education. This might increase the gap between parents' expectations and children’s attitudes and understanding of their education. Limitation: Community service activities were limited by time and frequency of meetings. Awareness should be increased more effectively by holding more meetings and conducting regular training on financial planning. Contribution: However, the program has contributed to initiating ideas and awareness in society.